The development of the therapeutic alliance and the emergence of alliance ruptures - Coutinho, Joana; Ribeiro, Eugénia; Fernandes, Catarina; Sousa, Inês; Safran, Jeremy D. (Anales de Psicología / Annals of Psychology, 2014)
Objectives: This study evaluated the development of the therapeutic alliance and the emergence of alliance ruptures, in a sample of patients with different diagnosis and different therapeutic outcome. Design: We examined the longitudinal data of 38 therapeutic dyads receiving cognitive-behavioural therapy, including dropouts as well as successful and unsuccessful cases. The sample included cases with Axis I and Axis II disorders.  Method: At the end of each session, patients evaluated the alliance using the Working Alliance Inventory (WAI). Six judges trained in the observation of alliance rupture markers with an observational system of ruptures, rated 201 videotaped sessions. Longitudinal statistical models were applied to the data. Results: We found that the pattern of alliance development of successful cases was different from the unsuccessful and dropouts cases. In addition on average, patients with personality disorders began therapy with a lower WAI score that decreased over time, whereas patients with Axis-I disorders began therapy with a higher WAI score that increased over time